Explosion limits of industrial spirit and their affecting by temperature. Issue 4 (18th March 2014) - Lepik, Petr; Mynarz, Miroslav; Serafin, Jiri; Bernatik, Ales
<x xml:space="preserve">Abstract</x> The article deals with the determination of industrial spirit's explosion limits and their affecting by temperature. It describes the determination of explosion limits and the influence of temperature by correlation equations available in professional literature, as well as the validation of these data by means of experiments in explosion autoclave and explosion chamber. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 380–384, 2014